MODEL EPIDEMIK DUA PENYAKIT DALAM SATU POPULASI - Yuni Yulida; Faisal Faisal; Dewi Anggraini (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
This paper considers a epidemic model for a spread of two diseases in a population. Fromthe model we study existence and stability of two equilibrium states: an infectious free equilibriumand an endemic equilibrium.